Sorbiochin – adsorbent for precious metals - Mohd Daud, Jamaluddin; Abd Rashid, Nur Suhaidah; Rabbani, Mohd Afif (2010)
Platinum, gold and palladium are precious metals which are widely used in industries for catalysts preparation, electronic components, electroplating, etc. Recovery of these trace metals in low concentration from solutions, plating bath, industrial effluents, etc. are essential for economic reasons and pollution prevention. One option is to use a separation technology based on solid phase extraction (SPE) for the recovery of low concentration of the precious metals. Sorbiochin, a melamine–chitosan–formaldehyde resin has been synthesize from biopolymer and was found suitable for preconcentration of trace amounts of. gold, platinum and palladium. The Sorbiochin is made into powders or discs and can be used to preconcentrate the precious metals from aqueous solutions. Sorbiochin adsorption of the precious metals is optimum at pH 1. The tendency of Sorbiochin to adsorb the precious metals is in the sequence of Pd(II) > Au(III)> Pt(II), and more than 5 - 50 mg of the metal ions can be adsorbed per gram of the resin. The precious metals can be desorbed almost completely from the resin by eluting with a common chelating agent.